Covalent fixing of sulfur in metal–sulfur batteries. Issue 2 (27th January 2020) - Fang, Ruopian; Xu, Jiangtao; Wang, Da-Wei
Abstract : This review proposes the concept of covalent fixing as a new research strategy for sulfur electrochemistry in advanced metal–sulfur batteries. Abstract : With its earth abundance and two-electron-transfer reaction mechanism, sulfur has been driving the rapid growth of metal–sulfur batteries. The practical performance of metal–sulfur batteries, however, is restricted by the notorious electrode processes of sulfur (such as low conductivity, intermediate loss, mass crossover, etc. ). Sulfur conversion reactions can be stabilized and promoted through a surface immobilization strategy via physical confinement and chemical adsorption effects. As an emerging method in the field, covalent-bonding sulfur materials have demonstrated promise for metal–sulfur batteries. The covalent fixing of sulfur reinforces the molecular interactions between sulfur and the cathode matrix at the bulk level. In this review, we attempt to address the covalent fixing concept on the basis of the emerging studies related to covalent sulfur-containing compounds and composites in various rechargeable metal–sulfur batteries. Firstly, we briefly discuss the classification of sulfur fixing strategies and identify the uniqueness of covalently stabilized sulfur for metal–sulfur batteries. Secondly, we summarize the state-of-the-art covalent sulfur-based materials as well as their synthetic chemistry. Thirdly, we focus on lithium–sulfur batteries that feature cathodes with covalent sulfur active materials, including reaction mechanisms and material innovations. Advances in alternative alkaline metal–sulfur battery systems (sodium–sulfur and potassium–sulfur) involving covalent fixing of sulfur are also discussed. Finally, the prospective opportunities of applying the covalent fixing strategy to optimize the sulfur redox process are commented on. This contribution is anticipated to place the covalent fixing of sulfur into the spotlight and to encourage more efforts in this challenging cross-disciplinary area of organic/polymer chemistry, materials science, electrochemistry and energy technologies.